Cardiopulmonary exercise testing in hepato-biliary & pancreas cancer surgery – A systematic review: Are we any further than walking up a flight of stairs?. (April 2018) - Kumar, R.; Garcea, G.
Abstract: Introduction: Cardiopulmonary exercise testing (CPET) is a reliable, reproducible and non-invasive measure of functional capacity. CPET has been increasingly used to assess pre-operative risk and stratify patients at risk of mortality and morbidity following surgery. CPET parameters that predict outcomes within liver and pancreas cancer surgery still remain to be defined. Methods: A systematic review to assess CPET use in predicting post-operative outcomes in liver and pancreas cancer surgery was carried out using the following databases AMED, CINAHL, Cochrane Library, EMBASE, Google Scholar and PubMED. Results: Data were extracted from four liver and four pancreas cancer studies. All were single institution, cohort series reporting outcomes with CPET used pre-operatively to assess patient morbidity, length of hospital stay and or mortality. In liver cancer surgery, all four papers reported outcome data on morbidity and patients who were more likely to suffer with complications tended to have an anaerobic threshold (AT) of less than 9.9–11.5 mL min −1 .Kg −1 . Whilst in pancreas cancer surgery, rates of pancreas fistulae tended to be higher in those patients who had an AT of less than 10 or 10.1 mL min −1 .Kg −1 . Discussion: The CPET variable most reported and relevant to morbidity in both liver and pancreas cancer surgery appeared to be AT. A pre-operative AT of approximately 10.5 mL min −1 .Kg −1 seems to be associated with a worse post-operative convalescence. Highlights: Cardiopulmonary exercise testing (CPET) is a reliable, reproducible and non-invasive measure of functional capacity. CPET has been increasingly used to assess pre-operative risk and stratify patients at risk of mortality and morbidity following surgery. CPET parameters that predict outcomes within liver and pancreas cancer surgery still remain to be defined. In liver cancer surgery, all four papers reported outcome data on morbidity and patients who were more likely to suffer with complications tended to have an anaerobic threshold (AT) of less than 9.9–11.5 mL min −1 .Kg −1 . Whilst in pancreas cancer surgery, rates of pancreas fistulae tended to be higher in those patients who had an AT of less than 10 or 10.1 mL min −1 .Kg −1 . The CPET variable most reported and relevant to morbidity in both liver and pancreas cancer surgery appeared to be AT. A pre-operative AT of approximately 10.5 mL min −1 .Kg −1 seems to be associated with a worse post-operative convalescence.